Off-grid sparse based two-dimensional direction of arrival estimation of acoustic vector sensor array in impulse noise. (October 2022) - Liang, Longkai; Shi, Yiran; Shi, Yaowu; Bai, Zhejia; He, Wenchao; Lv, Xuhao
In order to estimate the direction of arrival (DOA) of acoustic vector sensor, the phased fractional low-order moment (PFLOM) is used to suppress impulse noise. First, based on PFLOM, an off-gird sparse based two-dimensional (2D) DOA estimation model for acoustic vector sensor array is proposed. Then, a three-step alternating iterative Orthogonal Matching Pursuit (OMP) algorithm is introduced to realize the off-grid 2D DOA estimation, and the self-pairing of azimuth and elevation is achieved. Finally, the effectiveness and accuracy of the proposed algorithm under impulse noise and small snapshots are verified by simulation.